Oil Spills Simulation in Rayong Coastal Area: case study oil spill on 26 January 2022 - Polsomboon, Pongsit; Sriariyawat, Anurak (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
Oil spills cause severe problems to the environment and the economy. To manage the oil spill problem after it is released into the sea, it is necessary to know the current pattern and wind information. This study aimed to simulate the oil spill in Rayong coastal area on 26 January 2022 using the GNOME models. The GNOME model was calibrated using a satellite image from GISTDA when the severe oil spill event occurred near Samet Island on 27 July 2013. In the case of oil spills at Rayong coastal on 26 January 2022, the results have shown the oil spill will finally move to attack the Khao Leam Ya national park beach, which is around 9 km on the Eastern side of IRPC Industrial Estate, at 1.00 p.m. of 29 January 2022. Although the actual situation, the satellite image from GISTDA showed the oil spill moved to the coastal at 10.35 a.m. on 29 January 2022, faster than the model, about two and a half hours. This preliminary study will lead to further development to be accurate and precise. Further improvements in oil spill modeling should focus on another weathering process of spilled oil. The improvement in the parameterization of oil transport, since the accuracy of the transport process, depends on the accuracy of the circulation and atmospheric models.